Communicative Interaction among Local Editorial Staff Members: Current Situation and the Ways of its Improving - Korotitskaya, Mariya V.; Radchenko, Elena I.; Cherkashina, Anna A.; Narozhnyaya, Svetlana M.; Khovanova, Ekaterina V. (Journal of History Culture and Art Research, 2017)
Communication between management and employees is very important in organizations. However, communication problems might be more felt in any media organization as a whole and in the local media staff in particular. It’s obvious that news workers have everyday communicative interaction with different newsmakers. The article deals with the study and analysis of the communicative interaction between the local editorial creative staff members. Internal and external organizational understanding data are considered. It is determined that the level of organizational communication development influences the local editorial success and employees’ performance. Mutual understanding as the basic criterion of effective communication has several forms. The subject of our study is organizational understanding, that is, a special type of editorial staff relationship which is limited by the boundaries of the organization and is essential for its successful functioning and development. The analysis of empirical data allowed to identify the main problematic aspects and to work out the recommendations for vertical and horizontal communication development.